Konsep Dasar Perencanaan Pengajaran - Kurniawati, Dewi; R, Ridhohidayah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Teaching planning is a vital initial stage in the educational process, because without careful planning, the achievement of educational goals will be hampered. This article discusses the basic concept of teaching planning comprehensively, with an emphasis on the definition, principles, objectives, benefits, and main components in teaching planning. This study uses a qualitative approach with literature analysis as the main method. Based on the analysis, the results of this study indicate that good planning can improve the quality of learning, facilitate the teaching and learning process, and provide meaningful learning experiences for students. In addition, systematic teaching planning also plays a role in maximizing the use of time, resources, and increasing the efficiency of classroom management.